Analisis Partisipasi Dan Gaya Kepemimpinan Terhadap Intention To Stay Dan Kinerja Pegawai Di Dinas Pendidikan Kabupaten Nganjuk - Anita Pradnasari Dewi; Arisyahidin Arisyahidin (Otonomi, 2021)
The purpose of this study was to determine the effect of participation and leadership style on intention to stay and employee performance at the Nganjuk Regency Education Office, to determine the effect of participation on intention to stay and employee performance in the Nganjuk Regency education office and to determine the effect of leadership style on intention to stay and employee performance at the Nganjuk District Education Office. The population in this study were 65 employees of the Nganjuk Regency Education Office. In this study, the sample that will be used is a number of populations, as many as 60 employees of the Nganjuk District Education Office. The method of analysis used in this research is multiple linear analysis model. The results showed that participation and leadership style had an effect on Intention to Stay in the Nganjuk District Education Office simultaneously.There was a partial influence between participation on Intention to Stay and there was a partial influence between participation on employee performance.